2016
DOI: 10.1186/s40463-016-0174-y
|View full text |Cite
|
Sign up to set email alerts
|

One-and-a-half nostril endoscopic transsphenoidal approach for pituitary adenomas—a technical report

Abstract: BackgroundBinostril endoscopic transsphenoidal approach (BETA) provides sufficient manipulation space and wide endoscopic vision, although it increases the trauma of nose. Mononostril endoscopic transsphenoidal approach (META) has minimal trauma of nose, at the expense of space within the operation. We describe a one-and-a-half nostril endoscopic transsphenoidal approach (OETA) that combines the advantages of BETA and META.MethodsWe introduced OETA for pituitary adenomas with a detailed technical description. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…From the technical viewpoint, the mononostril approach is a two-hand technique, and the binostril and one and a half nostril approach can be a three-hand or four-hand technique. Endoscopes create a good and extensive visualization of the surgical field [6,7]. We compared these three approaches and techniques and consider the short-term and long-term outcomes, benefits, and complications of these three approaches for pituitary adenoma surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the technical viewpoint, the mononostril approach is a two-hand technique, and the binostril and one and a half nostril approach can be a three-hand or four-hand technique. Endoscopes create a good and extensive visualization of the surgical field [6,7]. We compared these three approaches and techniques and consider the short-term and long-term outcomes, benefits, and complications of these three approaches for pituitary adenoma surgery.…”
Section: Resultsmentioning
confidence: 99%
“…There is no prominent dissimilarity in the META and BETA groups but with a lower rate of improvement in the OETA group without any reasonable and sensible explanation (91.1% in META, 88% in BETA, and 73% in OETA) [7][8][9][10][11]. For more desirable surgical results and improvement of visual function, it is better to do an operation in the early stage of visual impairment before the occurrence of optic atrophy [20].…”
Section: Post-operative Visual Recoverymentioning
confidence: 94%
See 2 more Smart Citations
“…There were no instances of postoperative arterial epistaxis or severe complications in previous cohort of 57 patients undergoing the OETA. 11 The BETA placed the posterior nasal branch of the sphenopalatine artery 23 and some nasal septum nerves at a greater risk than the mononostril approach since it crosses the nasal septum. The meta-analysis 24 revealed that the BETA group had a higher rate of epistaxis than the META group.…”
Section: Discussionmentioning
confidence: 99%